Quantum Nature of Winter Depression - Adamski, Adam (Journal of Nutritional Therapeutics, 2013)
Depression is a disease that concerns a growing group of people: children, youth, adult and the elderly. Statistics indicate that 5 up to 20% of the population of the globe suffer from it. Women suffer from this disease four times more often than men. Depression is such a mental state in which the patient has a deep sense of meaninglessness of life and sees the world in the gloomy colors. Such a person is depressed, their mood affects the job, interpersonal relationships, and learning process. They have a feeling of hopelessness, worthlessness, pessimism and sadness. In many cases patients suffering from depression contemplate or attempt suicide. They cannot notice the solution of their problems. Moreover, they cannot imagine their future, if they were stopped in time. For such people only the past and their past failures matter. Time stopped for them. In addition to endogenous depression, there is also autumn-winter depression, which is a seasonal disease. The first symptoms appear in early autumn. The improvement of the patients’ mental health is observed from February whereas the next symptoms of the disease appear spontaneously in March and April. Winter depression is caused by a prolonged night in autumn and winter and this fact results in the prolonged synthesis of melatonin by the pineal gland, which affects the development of depression.